Intranasal Delivery of Recombinant S100A8 Protein Delays Lung Cancer Growth by Remodeling the Lung Immune Microenvironment - Wong, Sze Wing; McCarroll, Joshua; Hsu, Kenneth; Geczy, Carolyn L.; Tedla, Nicodemus (Frontiers in Immunology, 2022)
Lung cancer is the leading cause of cancer-related death worldwide. Increasing evidence indicates a critical role for chronic inflammation in lung carcinogenesis. S100A8 is a protein with reported pro- and anti-inflammatory functions. It is highly expressed in myeloid-derived suppressor cells (MDSC) that accumulate in the tumor microenvironment and abrogate effective anti-cancer immune responses. Mechanisms of MDSC-mediated immunosuppression include production of reactive oxygen species, nitric oxide, and depletion of L-arginine required for T cell function. Although S100A8 is expressed in MDSC, its role in the lung tumor microenvironment is largely unknown. To address this, mouse recombinant S100A8 was repeatedly administered intranasally to mice bearing orthotopic lung cancers. S100A8 treatment prolonged survival from 19 days to 28 days (p < 0.001). At midpoint of survival, whole lungs and bronchoalveolar lavage fluid (BALF) were collected and relevant genes / proteins measured. We found that S100A8 significantly lowered expression of cytokine genes and proteins that promote expansion and activation of MDSC in lungs and BALF from cancer-bearing mice. Moreover, S100A8 enhanced activities of antioxidant enzymes and suppressed production of nitrite, to create a lung microenvironment conducive to cytotoxic lymphocyte expansion and function. In support of this, we found decreased MDSC numbers and increased numbers of CD4+ T cells and natural killer T (NK-T) cells in lungs from cancer-bearing mice treated with S100A8, and ex-vivo treatment of splenocytes with S100A8 protein activated NK cells. Our results indicate that treatment with S100A8 may favourably modify the lung microenvironment to promote an effective immune response in lungs, thereby representing a new strategy that could complement current immuno-therapeutics in lung cancer.